Measurements of electroweak W jj production and constraints on anomalous gauge couplings with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (The European physical journal. C, Particles and fields, 2017)
Measurements of the electroweak production of a W boson in association with two jets at high dijet invariant mass are performed using s√= 7 and 8 TeV proton–proton collision data produced by the Large Hadron Collider, corresponding respectively to 4.7 and 20.2 fb−1 of integrated luminosity collected by the ATLAS detector. The measurements are sensitive to the production of a W boson via a triple-gauge-boson vertex and include both the fiducial and differential cross sections of the electroweak process.